The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/2842066
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting AraC-Resistant Acute Myeloid Leukemia by Dual Inhibition of CDK9 and Bcl-2: A Systematic Review and Meta-Analysis

Abstract: Purpose. This study aims to determine the influence of targeting araC-resistant acute myeloid leukemia by dual inhibition cyclin-dependent protein kinase (CDK9) and B-cell lymphoma-2 (Bcl-2). Method. The c-Myc inhibitor 10058-F4 and the CDK9 inhibitor AZD4573 were used to determine the cell cycle arrest and apoptosis. Results. 10058-F4 reduces c-Myc protein levels and suppresses HepG2 cell proliferation, possibly by upregulating cyclin-dependent kinase (CDK) inhibitors, p21WAF1, and reducing intracellular alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“… 103 A combination of AZD4573 and c-MYC inhibitor 10,058-F4 can effectively suppress araC-resistant AML. 119 …”
Section: Cdk9 Selective Inhibitors and Degraders And Combination Regimenmentioning
confidence: 99%
“… 103 A combination of AZD4573 and c-MYC inhibitor 10,058-F4 can effectively suppress araC-resistant AML. 119 …”
Section: Cdk9 Selective Inhibitors and Degraders And Combination Regimenmentioning
confidence: 99%
“…2 CDK9 forms the catalytic subunit of the positive transcription elongation factor b (P-TEFb), which is required for the phosphorylation of RNA polymerase II (RNA Pol II) C-terminal domain (CTD) and transcription elongation. [3][4][5] Dysregulation of the CDK9 pathway has been demonstrated in a range of cancers including acute myeloid leukemia, [6][7][8] prostate cancer, [9][10][11] and colorectal cancer. [12][13][14] It has been shown that CDK9 promotes the expression and activation of oncogenes, such as MYC and Mcl-1.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm can assist clinicians and medical personnel to a great extent. Acute lymphoblastic leukemia is a type of malignant blood cell cancer that affects mostly children and adults above age 65 [ 12 ]. Leukocytes, or white blood cells as they are commonly known, make up around one percent of all blood cells.…”
Section: Introductionmentioning
confidence: 99%